Toward standards in practices and techniques on ootaxonomy in the Pieridae (Lepidoptera: Papilionoidea) - Nieves-Uribe, Sandra; Llorente-Bousquets, Jorge; Flores-Gallardo, Adrián (Zootaxa, 2021)
We present a proposal on the standards used on ootaxonomy practices and techniques in the butterfly family Pieridae Duponchel (Lepidoptera: Papilionoidea) in five stages: 1) getting the specimens, 2) integration into a collection, 3) dissections to recover the exochorion, 4) elaboration of images of it, and 5) the preparation of its description with the necessary diagrams and tabulations. Also, we present the detailed techniques applied in observation and graphic representation, based on the methylene blue staining techniques and those required for the use with the scanning electron microscope (SEM). We compare the result of the standardized techniques with those from macro photography, drawings, and photographs with SEM—all of them found in books with descriptions and images of eggs of the Pieridae. We present a glossary and general aspects of the exochorion in the Pieridae as an Appendix to this article. Standardized techniques show more accurate and extensive character retrieval for systematics. For the scale in which they work, these techniques recovered more information than those present from oviposited eggs, where the exochorionic base is not seen. Also, the descriptions contain detailed data on more structures—which are comparable to each other—than are absent in the references mentioned. We present the recovered characters with the techniques found in the literature as three synthetically supplementary materials.